Inappropriate Birth Weight for Gestational Age Among Newborns Born at Dessie Referral Hospital: A Retrospective Cohort Study - Setegn Mihret; Kalkidan Wondwossen; Rodas Merid; Ketema Bizuwork Gebremedhin (International Journal of Pediatrics)
Inappropriate birth weight for gestational age (IBWGA) is linked with obstetric complications like birth asphyxia, hypothermia, and postpartum hemorrhage. This study was aimed at determining the prevalence of IBWGA with factors associated with newborns born at Dessie Referral Hospital, northeast of Ethiopia. We used a retrospective cohort study design and systematic random sampling method to select charts of women giving birth at the hospital from January 2013 to December 2017. Binary logistic regression analysis was used to check the association of selected variables with the outcome variable IBWGA. The prevalence of IBWGA was found to be 145 (34.36%), with 52 (12.32%) and 93 (22.04%) for large for gestational age (LGA) and small for gestational age (SGA), respectively. A higher prevalence of IBWGA was found among women who use substances during pregnancy, such as chewing chat (43, 49.4%), smoking (14, 53.8%), and those with a history of giving birth to an infant with IBWGA (31, 50.0%). Furthermore, maternal age less than 35 years old (p<0.05), antenatal care initiation at or before the second trimester (p<0.05), gestational age less than 37 weeks (p<0.05), and chewing chat during pregnancy (p<0.05) were found to be statistically significantly associated with IBWGA. The high prevalence of IBWGA revealed by this study suggests a need for interventions focusing on its predicting factors: maternal age, prenatal care, gestational age, and substance use during pregnancy.